2020
DOI: 10.1002/hipo.23262
|View full text |Cite
|
Sign up to set email alerts
|

New boundaries and dissociation of the mouse hippocampus along the dorsal‐ventral axis based on glutamatergic, GABAergic and catecholaminergic receptor densities

Abstract: In rodents, gene-expression, neuronal tuning, connectivity and neurogenesis studies have postulated that the dorsal, the intermediate and the ventral hippocampal formation (HF) are distinct entities. These findings are underpinned by behavioral studies showing a dissociable role of dorsal and ventral HF in learning, memory, stress and emotional processing. However, up to now, the molecular basis of such differences in relation to discrete boundaries is largely unknown. Therefore, we analyzed binding site densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 143 publications
(301 reference statements)
1
13
0
Order By: Relevance
“…Complementarily, increasing evidence shows spatial segmentation of function, neurotransmitter density and synaptic input occurs in a gradient along the longitudinal axis 64,65 . In several species and rodent strains, including in Sprague Dawley rats (the one used in this study), hABN have been reported to be in higher number in the dorsal than in the ventral hippocampus 66–71 .…”
Section: Discussionmentioning
confidence: 78%
“…Complementarily, increasing evidence shows spatial segmentation of function, neurotransmitter density and synaptic input occurs in a gradient along the longitudinal axis 64,65 . In several species and rodent strains, including in Sprague Dawley rats (the one used in this study), hABN have been reported to be in higher number in the dorsal than in the ventral hippocampus 66–71 .…”
Section: Discussionmentioning
confidence: 78%
“…The hippocampus is anatomically, neurochemically, and functionally subdivided along the septotemporal axis into dorsal, intermediate, and ventral regions [51][52][53][54]. While the dorsal hippocampus (dHPC) is mainly related to cortical regions and involved in cognitive processing, the ventral hippocampus (vHPC) has reciprocal projections to the amygdala and hypothalamus, and processes emotional and stress-related behaviors.…”
Section: The Amygdala-hippocampal-prefrontal Network In Depression and Anxietymentioning
confidence: 99%
“…However, Strange and colleagues suggested a gradient of functional hippocampal domains instead of precise distributed functions [37]. In addition, the neurochemical organization of the hippocampal formation evidences a high density of adrenergic receptors in the ventral region [54], which is relevant in stress response and depression and their links with decreased neurogenesis.…”
Section: The Amygdala-hippocampal-prefrontal Network In Depression and Anxietymentioning
confidence: 99%
“…It is now known that the HPC can be anatomically and functionally separated into dorsal and ventral subregions (posterior and anterior, respectively, in humans and non-human primates) (Fanselow and Dong, 2010;Bach et al, 2014) and the function of these discrete subregions is generally conserved across species (Ito and Lee, 2016). It is further postulated based on molecular and morphological signatures across the dorsalventral axis that a third intermediate subregion of the HPC should be considered when defining HPC subregions (Fanselow and Dong, 2010;Lothmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%